Paraovarian tumor of borderline malignancy – a case report. Issue 4 (1st June 2004) - De Areia, A. L. F. A.; Frutuoso, C.; Amaral, N.; Dias, I.; De Oliveira, C.
Abstract : A case of a 23-year-old woman with a paraovarian tumor is presented. The patient complained of pelvic pain and abdominal swelling. Cystectomy was the initial surgical treatment, but after the histological diagnosis, a staging surgery was carried out. The clinical aspects and subsequent management of related cases are discussed, and a literature review is made.